The Impact of Loop Electrosurgical Excision Procedure for Cervical Intraepithelial Neoplasia on Female Sexual Function (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Objective(s): Aim of the study was to find out the impact of LEEP (Loop Electrosurgical Excision) on overall sexual function in women with CIN.Materials and methods: This cross sectional study was performed at colposcopy clinic of Dhaka Medical College and Hospital from January 2016 to June 2016. Forty six women with CIN who underwent LEEP at least 6 months before were included in this study by purposive sampling. Face to face interview was taken with a preformed questionnaire on pre procedural sexual function and post-procedural sexual function.Results: Mean age of the women was 32.32 ±4.44 years (range 25 to 40 year). Time of resumption of sexual intercourse was 6.2 weeks on average. There was no change in coital frequency. About nine percent of women complaint of dyspareunia and vaginal dryness, 6.52% complaint of dissatisfaction to sexual intercourse, 10.87% felt lower abdominal pain after coitus and 13.1 % women felt decrease in sexual desire.Conclusion: LEEP for the treatment of cervical intraepithelial neoplasia doesnt significantly affect womens sexuality, when compared with sexual function before performing LEEP. Possible adverse effects may overcome by psychological counseling and healthy and hygienic life style.Bangladesh J Obstet Gynaecol, 2016; Vol. 31(2) : 81-85